PERLINDUNGAN HUKUM KONSUMEN TERHADAP TRANSAKSI JUAL BELI MELALUI LIVE STREAMING E-COMMERCE DI INDONESIA - Jenggis Khan Haikal (RESTORATIVE JUSTICE : Jurnal Hukum Universitas Muhammadiyah Kalianda, 2025)
The rapid development of live streaming e-commerce in Indonesia has transformed digital buying and selling patterns while simultaneously increasing consumer vulnerability due to the real-time, persuasive, and minimally documented nature of such transactions. This study aims to analyze consumer legal protection in buying and selling transactions conducted through live streaming e-commerce in Indonesia using the Digital Consumer Protection Model. The research employs a normative legal method with statutory and conceptual approaches. The findings indicate that although the Consumer Protection Law, the Electronic Information and Transactions Law, and the Personal Data Protection Law provide a legal foundation for consumer protection, these regulations have not yet fully adapted to the complexities of live streaming e-commerce transactions, particularly in terms of information transparency, multi-party accountability, and dispute resolution mechanisms. Therefore, strengthening digital consumer protection requires a more adaptive system-based approach that responds to the dynamics of the digital economy.